Elevated VCAM-1, MCP-1 and ADMA serum levels related to pulmonary fibrosis of interstitial lung disease associated with rheumatoid arthritis - Pulito-Cueto, Verónica; Remuzgo-Martínez, Sara; Genre, Fernanda; Atienza-Mateo, Belén; Mora-Cuesta, Víctor M.; Iturbe-Fernández, David; Lera-Gómez, Leticia; Sebastián Mora-Gil, María; Prieto-Peña, Diana; Portilla, Virginia; Blanco, Ricardo; Corrales, Alfonso; et al. (Frontiers in Molecular Biosciences, 2022)
Introduction: Early diagnosis of interstitial lung disease (ILD) associated with rheumatoid arthritis (RA) constitutes a challenge for the clinicians. Pulmonary vasculopathy is relevant in the development of ILD. Accordingly, we aimed to explore the role of vascular cell adhesion molecule-1 (VCAM-1), monocyte chemoattractant protein-1 (MCP-1) and asymmetric dimethylarginine (ADMA), key molecules in the vasculopathy, as potential biomarkers of pulmonary fibrosis inRA-ILD+. Methods: We included 21 RA-ILD+ patients and two comparative groups: 25 RA-ILD- patients and 21 idiopathic pulmonary fibrosis (IPF) patients. Serum levels of the molecules were determined by ELISA, and mRNA expression was quantified by qPCR. Results: VCAM-1, MCP-1 and ADMA serum levels were increased in RA-ILD+ patients in relation to RA-ILD- and IPF patients. Additionally, RA-ILD+ patients exhibited increased CCL2 (gene encoding MCP-1) and decreased PRMT1 (gene related to ADMA synthesis) mRNA expression in relation to RA-ILD- patients. A lower expression of VCAM1, CCL2, and PRMT1 was observed in RA-ILD+ patients when compared with those with IPF. Furthermore, MCP-1 serum levels and PRMT1 mRNA expression were positively correlated with RA duration, and ADMA serum levels were positively associated with C-reactive protein in RA-ILD+ patients. Conclusions: Our study suggests that VCAM-1, MCP-1 and ADMA could be considered as useful biomarkers to identify ILD in RA patients, as well as to discriminate RA-ILD+ from IPF, contributing to the early diagnosis of RA-ILD+.